2014
DOI: 10.5334/tohm.185
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin Therapy for Cervical Dystonia: The Science of Dosing

Abstract: The first-line treatment for cervical dystonia (CD) is botulinum toxin type A (BoNT-A), which has been established as a highly effective and well-tolerated therapy. However, this treatment is also complex and challenging to apply in clinical practice. Approximately 20% of patients discontinue therapy due to treatment failure, adverse effects, and other reasons. In addition, expert consensus recommendations are lacking to guide physicians in the optimal use of BoNT-A for CD. Among the issues still to be clarifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 44 publications
(112 reference statements)
0
13
0
1
Order By: Relevance
“…Two‐thirds to three‐quarters of shortened SCM patients reportedly experience severe pain in the neck, while other factors associated with the disability are fatigue, anxiety, depression, and decreased self‐efficacy (van den Dool et al, ). Oral medications such as baclofen, benzodiazepines, and anticholinergic agents are common treatments for shortened SCM, but they are associated with many side effects (Evidente and Pappert, ). As an alternative to such oral medications, BoNT injection has fewer side effects and confers greater improvements with regard to range of motion, correct posture, and pain management (Comella, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two‐thirds to three‐quarters of shortened SCM patients reportedly experience severe pain in the neck, while other factors associated with the disability are fatigue, anxiety, depression, and decreased self‐efficacy (van den Dool et al, ). Oral medications such as baclofen, benzodiazepines, and anticholinergic agents are common treatments for shortened SCM, but they are associated with many side effects (Evidente and Pappert, ). As an alternative to such oral medications, BoNT injection has fewer side effects and confers greater improvements with regard to range of motion, correct posture, and pain management (Comella, ).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have obtained significant improvements in head posture, pain, and quality of life with these therapies, with most patients reporting benefits of injection treatments (Nilesh and Mukherji, ). BoNT enhances the elasticity of the SCM, and its relieving effects appear immediately upon injection (Nilesh and Mukherji, ; Evidente and Pappert, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FDA approved the use of botulinum toxin A for cervical dystonia in 2000 and it is the first-line treatment for this condition. However, despite the use of botulinum toxin in cervical dystonia for over 20 years, there are still unanswered questions surrounding optimal dosing and dosing intervals [31]. Treatment failure is reported in 20% of patients [32].…”
Section: Cervical Dystoniamentioning
confidence: 99%
“…Double-blind, randomised clinical, as well as open, studies have shown that 50-85% of patients demonstrate a significant improvement [7][8][9][10][11][12][13][14][15]. A considerable number (c. 30%, range 19-46%) of patients discontinue treatment once it appears to be ineffective [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%